1996
DOI: 10.1002/hep.510230409
|View full text |Cite
|
Sign up to set email alerts
|

Admission levels of serum Gc-globulin: Predictive value in fulminant hepatic failure

Abstract: Gc-globulin scavenges actin released from necrotic he-the central nervous system with hepatic encephalopapatocytes to the extracellular space. In 77 patients with thy. 1 fulminant hepatic failure (FHF) (excluding patients A major problem in the treatment of FHF is the decitreated with liver transplantation), admission levels of sion of orthotopic liver transplantation (OLTx). [2][3][4][5] Early serum Gc-globulin and degree of complexing with mono-identification of patients at risk of dying is essential meric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 21 publications
5
30
0
Order By: Relevance
“…Our study con rms previous ndings of reduced levels of Gcglobulin and increased complex ratio in severe liver disease, especially in FHF (8)(9)(10)(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our study con rms previous ndings of reduced levels of Gcglobulin and increased complex ratio in severe liver disease, especially in FHF (8)(9)(10)(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 94%
“…In FHF, low Gc-globulin has been demonstrated to be associated with the development of the multiple organ dysfunction syndrome (MODS) (7). Low levels of total and 'free' (non-actin bound) Gc-globulin are indicators of a poor prognosis (8,9). Gc-globulin is also reduced in chronic liver disease (CLD), but to a lesser extent than in FHF (10).…”
mentioning
confidence: 99%
“…This confirms previous clinical studies in patients sustaining major trauma or fulminant hepatic failure (FHF) [4,5,11,12]. In these situations early serum concentrations of Gc-globulin were reduced combined with increased levels of Gc-globulin-actin complexes.…”
Section: Discussionsupporting
confidence: 78%
“…The search strategy identified 1427 studies potentially relevant of which 138 were retrieved, and 17 studies [11,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were found with enough information to go forward into a meta-analysis ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%